IMPLEMENTASI KEBIJAKAN KETERTIBAN UMUM TENTANG LARANGAN PEDAGANG ASONGAN DI KECAMATAN TANJUNG PRIOK JAKARTA UTARA - JOHANA, WILMA; POSUMAH, JOHNNY HANNY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2018)
presence of hawkers at Jakarta Capital Special Region (DKI Jakarta) does not fit with the vision of thecity, which mostly emphasizes the cleanliness,beauty and neatness of the city, therefore the policy of publicorder on the ban of hawkers. This policy is implemented throughout the Cityof Jakarta including in Tanjung Priok sub-district which on thisoccasion became the focus of the research. This research intend toexplain the implementation of public order policy on the ban ofhawkers In Tanjung Priok Sub-District, North Jakarta. The results of this study indicate that in terms ofstandars and policy targets that the goal of this policy is stillnotfully.Keyword : Implementation, Public Order Policy